Neglected ballistic trauma of the face in a young subject: A case report - Raiteb, Mohamed; Opoko, Ulrich; Sabr, Ayoub; Elmrini, Sanaa; Maadane, Amina; Slimani, Faiçal (Annals of medicine and surgery, 2021)
Injuries by ballistic projectiles concern nowadays more and more frequently civilian populations. If the vital prognosis is rarely put at risk, the functional after-effects are frequent and important. The management of these injuries follows specific rules that must be known because they are sometimes different from the usual traumatology. However, it is important for any surgeon to understand the basic principles of ballistic injury. Indeed, the knowledge of the trajectory of the bullet and its final location allows to consider the potential injuries and to evaluate the management of the patient. CT is the examination of choice for penetrating foreign bodies, allowing for viewing of the entry site, bullet trajectory, possible scattered fragments, and, most importantly, a possible skull base breach, as well as providing useful information for planning the surgical procedure and, generally, for prognosis. The primary surgery must ensure an early and rigorous trimming associated with antibiotic therapy because the quality of the initial trimming significantly influences the final result, so this approach to the removal of the foreign body depends on its size, its anatomical location, the structures involved and the preference of the surgeon. •Injuries caused by ballistic projectiles are nowadays more and more frequent in civilian populations.•Any surgeon or emergency doctor may be confronted with such traumas, the management of which is governed by specific rules that must be known because they are sometimes different from usual traumatology.•No physical theory can predict with certainty the behavior of a projectile in the human body.•The knowledge of the trajectory of the bullet and its final location allows us to consider the potential injuries and to evaluate the management of the patient.